Use of The Information System in The OMETV Application as A Means to Help Learning, Mastery And Development of Foreign Languages - Julianto; Tezar, Muhammad (SAINTEKBU, 2023)
The purpose of this research is to make it easier for students to use learning methods to help train mastery of foreign languages. The more developed an information technology and information system allows one to easily access various information that is spread on the internet. Not infrequently we can learn various learning media, especially foreign language material on the internet without having to take private lessons or take foreign language courses outside. OmeTV is a live video streaming application that is popular and easy to make this happen, allowing other ometv users from within the country and abroad to meet in the ometv room to simply interact, get to know each other, exchange cultures, entertain each other. others, even to train and hone, as well as develop mastery of foreign languages. The method applied in this research is the Literature Study method. The end result of using this method is useful information regarding the use of the OmeTV application.